2023
DOI: 10.1039/d2cc05900b
|View full text |Cite
|
Sign up to set email alerts
|

Surface charge-directed borophene–phosphorous nitride nanodot heterojunction supports for enhanced photoelectrochemical performance

Abstract: Complimentary surface-charged, nanosized 0D-0D hybrid of phosphorous nitride dots (PNDs) (ς = + 9.5 mV) and borophene dots (BDs) (ς =-26.2 mV) having favorable band alignments have been proposed for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Also, experimental investigations on borophene nanodot-based heterojunction displayed its potential for photoelectrochemical (PEC) water splitting. [83] The electrocatalytic HER activities of the above-discussed borophene-based catalysts were comparable to various 2D material-based catalysts from recent literature. Handoko et al [84] reported that the basal planes of a Mo-based MXene like Mo 2 CT x are active towards HER and showed η 10 of 189 mV and Tafel slope of 75 mV dec À 1 .…”
Section: Hydrogen Evolution Reaction (Her) and Oxygen Evolution React...supporting
confidence: 67%
See 1 more Smart Citation
“…Also, experimental investigations on borophene nanodot-based heterojunction displayed its potential for photoelectrochemical (PEC) water splitting. [83] The electrocatalytic HER activities of the above-discussed borophene-based catalysts were comparable to various 2D material-based catalysts from recent literature. Handoko et al [84] reported that the basal planes of a Mo-based MXene like Mo 2 CT x are active towards HER and showed η 10 of 189 mV and Tafel slope of 75 mV dec À 1 .…”
Section: Hydrogen Evolution Reaction (Her) and Oxygen Evolution React...supporting
confidence: 67%
“…Lastly, some research groups have explored various configurations derived from borophene, such as borophene nanoribbons, [81] borophene nanotubes, [82] borophene nanodots, [83] etc. The exciting activity of borophene nanoribbons and borophene nanotubes towards HER was explored through DFT studies.…”
Section: Catalytic Applicationsmentioning
confidence: 99%
“…The zeta potential measurements in Figure S5 evidenced the negative surface charge of borophene QDs at higher pH. In addition, Mohanta and Qureshi in 2023 also reported a zeta potential value (ς) of −26.2 mV for borophene dots . The effect of catalyst loading was evaluated by adding 15 –300 μL of QDs from the stock solution for the TMB oxidation reaction (Figure b).…”
Section: Resultsmentioning
confidence: 95%
“…In addition, Mohanta and Qureshi in 2023 also reported a zeta potential value (ς) of −26.2 mV for borophene dots. 53 The effect of catalyst loading was evaluated by adding 15 −300 μL of QDs from the stock solution for the TMB oxidation reaction (Figure 5b). The highest A 652 was obtained using 250 μL of QD solution for TMB chromogenic substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The borophene dot size was found to be 10 nm with an interplanar distance of 0.19 nm using TEM and HR-TEM, and other physicochemical validation were carried out using XRD, XPS, ultraviolet-visible spectroscopy, and photoluminescence spectroscopy. 38,39…”
Section: Synthesis Of Borophene Nanomaterialsmentioning
confidence: 99%